Poly(ADP-Ribose)Polymerase (PARP) Inhibitors and Radiation Therapy - Jannetti, Stephen A.; Zeglis, Brian M.; Zalutsky, Michael R.; Reiner, Thomas (Frontiers in Pharmacology, 2020)
Poly(ADP-ribose)polymerase-1 (PARP1) is a DNA repair enzyme highly expressed in the nuclei of mammalian cells, with a structure and function that have attracted interest since its discovery. PARP inhibitors, moreover, can be used to induce synthetic lethality in cells where the homologous recombination (HR) pathway is deficient. Several small molecule PARP inhibitors have been approved by the FDA for multiple cancers bearing this deficiency These PARP inhibitors also act as radiosensitizing agents by delaying single strand break (SSB) repair and causing subsequent double strand break (DSB) generation, a concept that has been leveraged in various preclinical models of combination therapy with PARP inhibitors and ionizing radiation. Researchers have determined the efficacy of various PARP inhibitors at sub-cytotoxic concentrations in radiosensitizing multiple human cancer cell lines to ionizing radiation. Furthermore, several groups have begun evaluating combination therapy strategies in mouse models of cancer, and a fluorescent imaging agent that allows for subcellular imaging in real time has been developed from a PARP inhibitor scaffold. Other PARP inhibitor scaffolds have been radiolabeled to create PET imaging agents, some of which have also entered clinical trials. Most recently, these highly targeted small molecules have been radiolabeled with therapeutic isotopes to create radiotherapeutics and radiotheranostics in cancers whose primary interventions are surgical resection and whole-body radiotherapy. In this review we discuss the utilization of these small molecules in combination therapies and in scaffolds for imaging agents, radiotherapeutics, and radiotheranostics. Development of these radiolabeled PARP inhibitors has presented promising results for new interventions in the fight against some of the most intractable cancers.